12. letno srečanje Združenja za slovansko jezikoslovje = 12th Slavic Linguistics Society Annual Meeting = XII ежегодная конференция Общества славянского языкознания Povzetki prispevkov = Book of abstracts = Тезисы докладов - Repanšek, Luka; Šekli, Matej (ZRC SAZU, Založba ZRC, 2017)
The 12th Slavic Linguistics Society Annual Meeting organised by the Fran Ramovš Institute of the Slovenian Language (Research Centre of the Slovenian Academy of Sciences and Arts), Department of Slavistics, Department of Slovenian Studies and the Department of Comparative and General Linguistics (Faculty of Arts, University of Ljubljana) held in Ljubljana between 21 and 24 September 2017 hosted a remarkable 100-odd Slavicists from Northern America, Europe, Russia, South Korea and Japan. The multifariousness of linguistic enquiry and methodology characterising the resultant book of abstracts celebrates the overall importance and responsibility of methodological pluralism that is the driving force behind the constructive dialogue fostered at any scientific meeting.